Natural orifice transluminal endoscopic surgery in humans: feasibility and safety of transgastric closure using the OTSC system - Magdeburg, Richard; Kähler, Georg (Surgical endoscopy and other interventional techniques, 2016)
Background: NOTES is a technique in which an operation is performed within the body without a skin incision by using a natural body orifice to provide access. The principal challenge of transgastric NOTES procedures is still the feasibility and safety of access closure. Currently, there are very limited data regarding the closure of transgastric NOTES in humans, and the standard method and device for closure has not been defined. Herein, we evaluate the feasibility and safety of gastric closure after NOTES procedures in humans with the over-the-scope clip (OTSC). Methods: Review of collected data of patients underwent transgastric NOTES in prospective clinical studies between April 2010 and March 2014 focused on the gastric closure with the OTSC. Results: A total of 43 patients underwent transgastric NOTES: 36 patients with an acute appendicitis, six patients with a prophylactic bilateral salpingo-oophorectomy, and one patient with uterus myomatosus. In all 43 cases, the incision of the gastric wall and the endoscopic access to the abdominal cavity succeeded without any difficulty. After performing transgastric procedures, it was possible to close the access by OTSC in all cases. There were all in all three adverse events: one major (Clavien-Dindo Grade III) and two minor (Clavien-Dindo Grades I and II). Conclusion: Even if we could show for the first time in more than 40 consecutive patients that there is a safe approach for closing the transgastric access, it is absolutely necessary that further investigation in clinical settings has to be done to establish clear indications and guidelines for the use of transgastric NOTES.